2018
DOI: 10.1111/ejn.13943
|View full text |Cite
|
Sign up to set email alerts
|

Nonuniform impacts of forward suppression on neural responses to preferred stimuli and nonpreferred stimuli in the rat auditory cortex

Abstract: In natural conditions, human and animals need to extract target sound information from noisy acoustic environments for communication and survival. However, how the contextual environmental sounds impact the tuning of central auditory neurons to target sound source azimuth over a wide range of sound levels is not fully understood. Here, we determined the azimuth-level response areas (ALRAs) of rat auditory cortex neurons by recording their responses to probe tones varying with levels and sound source azimuths u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…In the present study, the azimuth functions of AI neurons obtained from two control groups demonstrated that more than half of the neurons in the rat AI preferred sound stimuli from the contralateral azimuth in the horizontal plane. This is consistent with the findings shown in previous studies regarding the spatial representation of rat AI neurons measured by spike counts (Yao et al, 2013; Gao et al, 2018) and excitatory postsynaptic potentials (Chadderton et al, 2009). Studies using interaural level differences to mimic the changes of spatial azimuth also demonstrated that most tested neurons in the rat AI preferred acoustic stimuli from contralateral horizontal positions (Kelly and Sally, 1988).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the azimuth functions of AI neurons obtained from two control groups demonstrated that more than half of the neurons in the rat AI preferred sound stimuli from the contralateral azimuth in the horizontal plane. This is consistent with the findings shown in previous studies regarding the spatial representation of rat AI neurons measured by spike counts (Yao et al, 2013; Gao et al, 2018) and excitatory postsynaptic potentials (Chadderton et al, 2009). Studies using interaural level differences to mimic the changes of spatial azimuth also demonstrated that most tested neurons in the rat AI preferred acoustic stimuli from contralateral horizontal positions (Kelly and Sally, 1988).…”
Section: Discussionsupporting
confidence: 93%
“…Most of the neurons in AI preferred sound stimuli from the contralateral field, and only a small proportion of neurons preferred the sound stimuli from midline or ipsilateral field. This has been demonstrated in cats (Imig et al, 1990; Rajan et al, 1990; Barone et al, 1996; Eggermont and Mossop, 1998), rats (Yao et al, 2013; Gao et al, 2018), and monkeys (Woods et al, 2006). Studies also showed that many azimuth-sensitive neurons in the AI of adult cats determined in binaural conditions immediately became insensitive to sound source azimuth when determined with one ear plugged (Samson et al, 1994), demonstrating the importance of normal binaural input in the spatial sensitivity of AI neurons.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our data show that majority of AI neurons preferred ILDs favoring contralateral spatial azimuth in both the adult and developing rats (Figure 8). Studies in the adult animals in a variety of species have demonstrated the dominant preference of AI neurons to contralateral spatial locations, e.g., in cats (Irvine et al, 1996;Zhang et al, 2004), bats (Razak, 2011), monkeys (Zhou and Wang, 2012;Lui et al, 2015), rats (Yao et al, 2013;Gao et al, 2018;Wang et al, 2019), and mice (Panniello et al, 2018). The results in the immature rats suggest that the dominant contralateral preference of AI neurons is already present immediately after the onset of hearing and is adult-like.…”
Section: Postnatal Development Of Interaural Level Differences Processing In the Auditory Cortexmentioning
confidence: 96%
“…Lesion or inactivation of AI leads to sound localization deficits (Malhotra and Lomber, 2007;Nodal et al, 2010). AI neurons have been shown to be sensitivity to sound-source azimuth in cats (Samson et al, 1994), monkeys (Woods et al, 2006), bats (Razak, 2011), ferrets (Wood et al, 2019), and rats (Yao et al, 2013;Gao et al, 2018;Wang et al, 2019). The spatial sensitivity of AI neurons to sound-source azimuth largely depends on binaural processing.…”
Section: Introductionmentioning
confidence: 99%